The Occurrence of Serotypes and Virulence Genes of Listeria monocytogenes in Various Food Products - Raeisi, M.; Afshari, A.; Shirzad-Aski, H.; Seifi, S.; Hashemi, M.; Khoshbakht, R.; Noori, S.M.A. (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Given that controlling Listeria contamination is very important in food chain system, the knowledge of their prevalence in food is very important. Therefore, this study aims to examine the prevalence of important Listeria species in various food types and evaluate serotype distribution, as well as the study of the virulence factors of L. monocytogenes. Methods: During July 2018 and January 2020, 900 food samples were collected in the North of Iran, including beef, chicken, fish, shrimp, milk and yogurt, green vegetables, mixed vegetable salad, Olivier salad, and cottage cheese. After isolation and identification steps, each bacterial DNA was extracted. Then, using specific primers, species, serotypes, and virulence genes of Listeria isolates were evaluated in the samples by Polymerase Chain Reaction (PCR) method. Results: The test results of 136 samples (15.1%) were positive for Listeria spp. and the most contaminated food was beef (35%) followed by chicken (29%) and green vegetables (23%). The most isolated Listeria spp. was L. monocytogenes and L. ivanovii. Among L. monocytogenes isolates, the dominant serogroups were 1/2a and 4b; furthermore, all of the isolates of this species harbored four virulence genes, including hlyA, plc, iap, and actA. Conclusion: These reports highlighted the importance of food safety in various food products, particularly raw meats and vegetables. Moreover, contamination of healthy foods such as fish and vegetables with Listeria is an indicator of public health. © 2023, Shahid Sadoughi University of Medical Sciences. This is an open access article under the Creative Commons Attribution 4.0 International License.
Keywords: Food Contamination; Listeria monocytogenes; Polymerase Chain Reaction; Serotyping